The haemodynamic and ventilatory responses with I-gel, laryngeal mask airway and tracheal intubation during laparoscopic cholecystectomy - Maharjan, SK (Journal of Kathmandu Medical College, 2013)
Background: Despite use of adequate medications and techniques, tracheal intubation induces haemodynamic stress response, which can be minimized by using supraglottic airway devices instead of tracheal tube in elective surgical cases with adequate oxygenation and ventilation. Objectives: To compare haemodynamic variables and ventilation parameters of I-gel and laryngeal mask airway with tracheal intubation during laparoscopic surgery. Methods: This is a prospective randomized comparative study among 90 cases of American Society of Anesthesiologists physical status class I and II, undergoing laparoscopic cholecystectomy, who were equally divided into three groups of 30 patients each: I-gel group, Laryngeal mask airway group and Tracheal tube group. Randomization was done with pick up of cards from sealed envelope. Basal readings of heart rate, systolic, diastolic and mean arterial pressure were recorded and these parameters were measured again before airway device placement, one, three and five minutes after airway manipulation, during carboperitoneum creation and before and after extubation. Oxygen saturation, end tidal CO2, airway pressure and inhaled and exhaled tidal volume and minute volume were monitored before, during and after carboperitoneum creation. Leak volume was calculated by deducing exhaled tidal volume from inhaled tidal volume. Statistical analysis (Analysis of variance test) was done to see the differences among the groups. Results: Haemodynamic perturbations were maximum with tracheal intubation and moderate with laryngeal mask airway while stable haemodynamics was observed with I-gel. Intra and inter-group comparison revealed significant differences after use of airway devices and after removal as well. Regarding ventilatory response, oxygenation and ventilation was well maintained with maximum airway pressure of mean ± SD: 20.11 ±3.46, 20.24 ±4.42, 19.05±4.82 cmH2O during carboperitoneum creation in I-gel, laryngeal mask airway and tracheal tube group respectively and oxygen saturation of 98 to 100% and end tidal CO2 level of 31-35 mmHg. In all groups, minute volume was well maintained and leak volume of 18.88±12.40, 17.13±13.32 and 20.89±12.20 ml were recorded in I-gel, laryngeal mask airway and tracheal tube group respectively during carboperitoneum creation. There was no statistically significant difference among the groups at any time regarding the monitored parameters. Conclusion: Among the three airway management devices used during general anaesthesia with positive pressure ventilation, I-gel produced least haemodynamic stress response, both supraglottic devices can be used with proper size and placement with acceptable haemodynamics and ventilation during laparoscopic surgery. DOI: http://dx.doi.org/10.3126/jkmc.v1i2.8143 Journal of Kathmandu Medical College, Vol. 1, No. 2, Oct.-Dec., 2012: 84-90